2003
DOI: 10.1089/152308603768295113
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of ER Resident Proteins Upon Oxidative Stress: Effects of Altering Cellular Redox/Antioxidant Status and Implications for Protein Maturation

Abstract: Previous work showed that from all cellular proteins, the endoplasmic reticulum (ER) resident proteins are most sensitive to oxidative stress [hydrogen peroxide (H(2)O(2))], as determined using the oxidation-sensitive, membrane-permeable, acetylTyrFluo probe. Because of the importance of these proteins in proper cellular functioning, we studied (a) whether modifying the cellular redox state/antioxidant status alters the susceptibility of those proteins toward H(2)O(2) oxidative stress and (b) whether H(2)O(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 20 publications
1
61
0
Order By: Relevance
“…25 Additionally, ROS can directly perturb redox homeostasis within the ER lumen, which specializes in protein folding and disulfide bond formation, 26 and can even cause oxidative damage to ER-resident proteins directly or indirectly through lipid peroxidation. 27,28 All of these features evoke the idea that ROS induce misfolded protein accumulation and the subsequent ER stress response, but such reports are scarce. Here, in a model of myocardial I/R, we have demonstrated for the first time that excess production of ROS, especially superoxide, after reperfusion has a critical role in activating the ER stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Additionally, ROS can directly perturb redox homeostasis within the ER lumen, which specializes in protein folding and disulfide bond formation, 26 and can even cause oxidative damage to ER-resident proteins directly or indirectly through lipid peroxidation. 27,28 All of these features evoke the idea that ROS induce misfolded protein accumulation and the subsequent ER stress response, but such reports are scarce. Here, in a model of myocardial I/R, we have demonstrated for the first time that excess production of ROS, especially superoxide, after reperfusion has a critical role in activating the ER stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…6,23,24 On the other hand, ROS is thought to be a cause of ER stress via several mechanisms, 2,7,8,[25][26][27][28] but whether the ROS overproduction after myocardial I/R triggers the CHOP-related ER stress response remains unclear. Thus, we assessed the potential effects of edaravone, a free radical scavenger clinically available in Japan, 29 on regulation of ER stress after myocardial I/R.…”
Section: I/r-induced Ros Generation Triggers the Chop-related Er Strementioning
confidence: 99%
“…These lipid peroxides could have resulted from triglyceride peroxidation under oxidative stress. Endoplasmic reticulum resident proteins are known to be most sensitive to oxidative stress (41)(42)(43), but no data are available yet on the effect of oxidative stress on DGAT1 activity. We have now clearly demonstrated that in PON2-deficient MPMs that were treated with the free radical generator AAPH, the cellular oxidative stress increased, followed by an increment in DGAT1 activity.…”
Section: Pon2 Inhibits Macrophage Triglyceride Biosynthesis 877mentioning
confidence: 99%
“…Conversely, ROS accumulation can induce the oxidation of resident ER proteins, including proteins of the polypeptide folding machinery such as PDI and BiP (van der Vlies et al. 2002, 2003), thus leading to an ER stress and creating a vicious cycle (Malhotra and Kaufman 2007). To alleviate the deleterious effects of ROS, the PERK branch of the UPR can activate the transcription of several key antioxidant enzymes via the phosphorylation of nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) (Cullinan and Diehl 2006; Flamment et al.…”
Section: Introductionmentioning
confidence: 99%